(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Witasari LD, Huang FC, Schwab W. 2022. Identification and characterization of strawberry FvGELP1 (Fragaria vesca GDSL esterase/lipase).Biodiversitas 23: 907-915. Fruit softening is primarily the result of the hydrolytic enzymes activity. Esterases are reasonable candidates due to their putative role in cell wall components degradation. This study aimed to identify and characterize a new enzyme related to strawberry fruit ripening. Esterase activity was detected in the native PAGE of protein extract isolated from Fragaria ×ananassared fruit. Amino acid sequence analysis of the protein band revealed several esterases as possible candidates. GDSL esterase/lipase from Fragaria vesca(gene27964; FvGELP1) was chosen for cloning purposes and further analysis. Quantitative RT-PCR of FvGELP1in plant tissues of F. vescaindicated high expression levels in fruit, in particular in early developmental stages. The gene FvGELP1(1,161 bp) was amplified from F. vescafruit cDNA and expressed as a 43 kDa HisTag fusion protein in Saccharomyces cerevisiae.FvGELP1 possesses four conserved residues Gly43-Asp44-Ser45-Asn46. FvGELP1 contains Ser45, Asp364, and His367 as the catalytic triad. Esterase assays of FvGELP1 resulted in high levels of the aromatic alcohol products by applying ?-naphthyl acetate (?NA), p-nitrophenyl acetate (pNPA), phenyl acetate, and benzyl acetate as substrates. It could be suspected that FvGELP1 plays a role in strawberry fruit ripening and might be involved in the hemicellulose degradation, presumably by deacetylation of the polysaccharide.